2017
DOI: 10.1093/jmcb/mjx050
|View full text |Cite
|
Sign up to set email alerts
|

CDYL1 fosters double-strand break-induced transcription silencing and promotes homology-directed repair

Abstract: Cells have evolved DNA damage response (DDR) to repair DNA lesions and thus preserving genomic stability and impeding carcinogenesis. DNA damage induction is accompanied by transient transcription repression. Here, we describe a previously unrecognized role of chromodomain Y-like (CDYL1) protein in fortifying double-strand break (DSB)-induced transcription repression and repair. We showed that CDYL1 is rapidly recruited to damaged euchromatic regions in a poly (ADP-ribose) polymerase 1 (PARP1)-dependent, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 58 publications
1
54
0
Order By: Relevance
“…This process, which remained unaffected by ATM inhibition (Pankotai et al 2012), is mediated by the ubiquitylation and eviction of RNAPII. In contrast, DSBs generated in close proximity to a gene lead to its transient repression through ATM-or PARP-1-mediated chromatin remodeling, which induces a chromatin context that is repressive for transcription (Shanbhag et al 2010;Kakarougkas et al 2014;Gong et al 2015Gong et al , 2017Ui et al 2015;Ui and Yasui 2016;Awwad et al 2017;Abu-Zhayia et al 2018;Gong and Miller 2018).…”
Section: Dna-pk-and Wwp2-dependent Transcription Silencing Is Unique mentioning
confidence: 99%
See 2 more Smart Citations
“…This process, which remained unaffected by ATM inhibition (Pankotai et al 2012), is mediated by the ubiquitylation and eviction of RNAPII. In contrast, DSBs generated in close proximity to a gene lead to its transient repression through ATM-or PARP-1-mediated chromatin remodeling, which induces a chromatin context that is repressive for transcription (Shanbhag et al 2010;Kakarougkas et al 2014;Gong et al 2015Gong et al , 2017Ui et al 2015;Ui and Yasui 2016;Awwad et al 2017;Abu-Zhayia et al 2018;Gong and Miller 2018).…”
Section: Dna-pk-and Wwp2-dependent Transcription Silencing Is Unique mentioning
confidence: 99%
“…Finally, PARP1 triggers the recruitment of chromodomain protein Y-like (CDYL1), which negatively regulates transcription through histone H3K27 methylation (Abu-Zhayia et al 2018). While NELF promotes DSB repair via both NHEJ and HR, KDM5a, ZMYND8-NuRD, and CDYL1 promote DSB repair through HR only (Gong et al 2015(Gong et al , 2017Abu-Zhayia et al 2018). Together, these studies revealed that ATM and PARP1 silence transcription of genes that flank DSBs by triggering extensive chromatin remodeling around the damage, thereby promoting efficient repair by NHEJ and HR.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…During DNA damage-induced transcription silencing, PARP1 facilitates the recruitment of the polycomb repressive complex 1 and 2 (PRC1 and PRC2), ensuring the proper chromatin structure and transcription arrest at the damaged sites [44,47]. Moreover, the chromodomain Y like (CDYL) protein interacts with PRC2 in a PARP-dependent manner [48,49]. During DSB-induced transcription silencing, PARP1 promotes the recruitment of KRAB-associated protein-1 (KAP-1), heterochromatin protein 1 (HP1), and suppressor of variegation 3-9 homolog 1 (SUV39H1) ( Figure 3A) [50].…”
Section: Parylation Regulates Transcription Responses During Dna Damagementioning
confidence: 99%
“…Not surprisingly, both CDYL and G9a are upregulated in hepatocellular carcinoma (HCC), but not in non-cancerous liver tissues 20 . CDYL1 also associates with chromatin assembly factor 1 (CAF1) and the MCM complex, and recruits histone H3K9/27 methyltransferases G9a, SETDB1, and PRC2 to the replication forks for transmission of repressive chromatin marks during DNA replication 21 , or to DNA double-strand break (DSB) sites for transcriptional silencing and promotion of homology-directed DNA repair (HDR) 22 .…”
Section: Introductionmentioning
confidence: 99%